Karakteristik Morfologi Fase Vegetatif Berbagai Varietas Jeruk Pamelo Pangkep dengan Teknik Sambung Mini - Kafrawi Kafrawi; Zahraeni Kumalawati (Fakultas Pertanian, Universitas Syiah Kuala, 2008)
Morphology Characteristics of Vegetatif Phase on Several Varieties Pangkep Pummelo (Citrus maxima) with Mini Grafting TechniqueABSTRACT. The main objective of this research was to learning several stump effect to morphology characteristics of vegetatif phase of several varieties pangkep pummelo and to know various stump was compatible to growty support several pummelo pangkep. The project was conducted in green house and laboratory of Politani Pangkep, South Sulawesi from April to November 2007. The experiment was design in randomized block design consisted of two factors. Firstly, several entres pummelo i.e. pangkep merah, pangkep putih and sigula-gula. The second factor was several stump various pummelo i.e. swingle citrumelo, pangkep merah, pangkep putih and si gula-gula. The result showed pangkep merah pummelo have better vigor was use entres or stump. All growth variants show pangkep merah pummelo induced statistically significant effect (caulis diameter, bud length bud, sum bud, leaf area, root length, moisture content of root and tree).